Estimación del impacto económico de las inversiones realizadas por Iniap, en generación y transferencia de tecnologías, en el cultivo de soya, durante el periodo, 2000–2012 - Álava Onofre, Giancarlo Emanuel (2014)
This research analyzes the Economic Impact of Investments Made by lNlAP, Generation and Technology Transfer in Soybean crops during the period 2000-2012. To which based on the calculation of the economic surplus model, where an average rate of return to investment in research based on calculated as a percentage of the increase in production is estimated benefits due to technological change was used This investment showed a return of 68.48 % which proves that investments in research and technology transfer were and are profitable. This high cost is due to the effective work of lNlAP in the generation and dissemination of new technologies for sojeras area of Ecuador, and ongoing research being conducted to improve varieties and thus achieve high adoption of materials generated accompanied their respective technological recommendations.